Effectiveness of multi position, electrostatic and nanofluid based minimum quantity lubrication: A brief review. (2020) - Ranjan Mishra, Rasmi; Bag, Rabinarayan; Panda, Amlana; Kumar, Ramanuj; Kumar Sahoo, Ashok
Abstract: Dry cutting is considered to unveil the lower process efficiencies while the flood cooling approach is striving for the higher cost, health, and environmental predicament. The effectual lubrication and cooling approach are essential to control the quantity of heat produced through cutting. Because the emerged heat if not managed properly, this negatively influences the process performance in terms of machined surface characteristics, cutting tool wear and power consumption in machining practice. The incumbent research on Minimum Quantity Lubrication (MQL) provides high-quality cutting performance together with de-escalated machining cost performing the metal cutting processes more environment-friendly and sustainable. The lubrication condition plays a deep-seated effect on performance of the product; therefore the timely selection of coolant is very vital particularly during cutting of hardened steel and hard-to-cut materials with desirable cutting parameters. The effects of coolants on the machining performance of hard part material are significant for better understanding to advance their functional performance. Therein, the purview of this concise report is to converge an appropriate framework for the real-time selection of cutting and machining fluid factors for ecological and cost-effective feasible manufacture of quality parts in Multi-position, Electrostatic and Nano based Minimum Quantity Lubrication approach.